Corrosion Mitigation by an Eco-Friendly Inhibitor: Nerium Oleander Leaf Extract on Carbon Steel in an Acidic Medium - Selvi,Arockia (2020)
The inhibitory activity of ethanol extract of Nerium oleander leaf (NOLE) on carbon steel corrosion in 0.5 M and 1.0 M of hydrochloric acid solutions was studied by weight loss method and electrochemical techniques. The inhibition efficiency (h w) increased with an increase in the concentration of NOLE and in temperature. Polarisation curves indicated that NOLE acts as a mixed type of inhibitor. The changes in charge transfer resistance (Rt) with increasing inhibitor (i.e. NOLE) concentration assured the adsorption of the inhibitor onto the metal surface. The results of h w, h p (inhibition efficiency obtained from polarisation study) and hR (inhibition efficiency obtained from impedance analysis) are in par with each other. Surface morphology study uncovered the coating of the inhibitor molecule on the metal surface. The phenomenon of physical adsorption has been established based on the inhibition efficiency of the inhibitor with change in temperature.